The Effectiveness of Counseling through Vasectomy Module in North Kolaka, Indonesia - Askrening Askrening; Hendra Yulita (Intelektual Pustaka Media Utama, 2017)
The main problem faced nowadays is the low participation of men in terms of implementation of the Family Planning Program. The figures for family planning in Indonesia only demonstrate a high rate on contraception use in women not in men. The Strategy to improve knowledge by promotion activities of family planning of men with a variety of media and forms are expected to increase knowledge. This study aimed to analyze the effectiveness of media modules to improve knowledge and attitudes and also analyze the factors that lead to low participation of family planning in North Kolaka. This study used Mixed Method design which combines qualitative and quantitative method. The research was conducted in North Kolaka in July and August 2016. The population of this study was all of husbands who classified as a couple reproductive ages in North Kolaka with the total of 19,819 people. Samples were divided into two groups: the experimental group given counseling through modules about vasectomy were 124 people and the control group given counseling without a module were 126 people.The module is more effective to improving knowledge and attitudes than counseling without module. The most reason for rejection vasectomy was they want to have children, fear of surgery and religious issues. Health promotion through modules must be expanded and improved by the district government of North Kolaka. Implementing promotion programs shouldnt involve religious leaders.